Nonmaximal Entanglement Can Make Joint Remote State Preparation Absolutely Secure - Bich, Cao Thi; An, Nguyen Ba (Communications in Physics, 2013)
Joint remote state preparation is a multiparty global quantum task in which several parties are assigned to jointly prepare a quantum state for a remote party. Although various protocols have been proposed so far, none of them are absolutely secure in the sense that the legitimate parties (the preparers plus the receiver) can by no means identify the state to be prepared even if they all collude with each other. Here we resolve this drawback by employing the quantum channel in terms of nonmaximally entangled states whose parameters are kept secret to all the participants but used to split the information in a judicious way so that not only absolute security in the above-mentioned sense is achieved but also the performance is the simplest possible.